The Role of Non-State Actors in the Green Transition : Building a Sustainable Future. - Hoff, Jens; Gausset, Quentin; Lex, Simon (Routledge explorations in environmental studies., 2019)
This book argues that there is no way to make progress in building a sustainable future without extensive participation of non-state actors. The volume explores the contribution of non-state actors to a sustainable transition, starting with citizens and communities of different kinds and ending with cities and city-networks. The authors analyse social, cultural, political and economic drivers and barriers for this transition, from individual behaviour to structural restraints, and investigate interplay between the two. Through a series of wide-ranging case studies from the UK, Australia, Germany, Italy and Denmark, and a number of comparative case studies, the volume provides an empirically and theoretically robust argument that highlights the need to develop, widen and scale up collective action and community-based engagement if the transition to sustainability is to be successful. This book will be of great interest to students and scholars of climate change, sustainability and environmental policy.